2014
DOI: 10.1007/s00256-014-2044-x
|View full text |Cite
|
Sign up to set email alerts
|

Segond fracture: involvement of the iliotibial band, anterolateral ligament, and anterior arm of the biceps femoris in knee trauma

Abstract: Associated findings of Segond fracture include ACL tear, MCL tear, medial meniscus tear, and posterolateral corner injury. Both the ITB and the ALL may be involved in the Segond avulsion. The anterior arm of the biceps femoris tendon is not involved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 14 publications
2
59
0
3
Order By: Relevance
“…The small ALL thickness and its anatomical variability also difficult the complete visualization. 5,11,12 Helito et al 5 performed a study in 39 patients and identified the ALL in its entirety in around two-thirds of the MRI scans, but additional coronal proton densityeweighted sequences without fat saturation were also used. Taneja et al, 13 in a study of 70 patients, were able to visualize the ALL in its entirety in a very low percentage of the MRI scans, observing some portion of the ligament in around half of the scans.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The small ALL thickness and its anatomical variability also difficult the complete visualization. 5,11,12 Helito et al 5 performed a study in 39 patients and identified the ALL in its entirety in around two-thirds of the MRI scans, but additional coronal proton densityeweighted sequences without fat saturation were also used. Taneja et al, 13 in a study of 70 patients, were able to visualize the ALL in its entirety in a very low percentage of the MRI scans, observing some portion of the ligament in around half of the scans.…”
Section: Discussionmentioning
confidence: 99%
“…Both of these studies found a low percentage of Segond fractures; thus, these fractures cannot be the only indication of ALL injury or associated anterolateral instability. Claes et al 19 suggested that Segond fractures are always related to a bone avulsion of the ALL; however, De Maeseneer et al 11 found that the iliotibial band may also be involved in the genesis of this avulsion. Davis et al 20 identified 2 cases of injury of the knee lateral complex, comprising the ALL and lateral collateral ligament.…”
Section: And Duthonmentioning
confidence: 98%
See 1 more Smart Citation
“…La localización de la inserción tibial del LAL posterior al tubércu-lo de Gerdy (1,(8)(9)(10)(11)39,40) y la frecuente combinación con la lesión del LCA hacen que se haya relacionado la lesión de esta estructura con la fractura de Segond (9,27,28) . La banda iliotibial (5,68,69) , la zona central de la cápsula articular (6,67) , el brazo anterior de la cabeza corta del bíceps femoral (70) y la banda anterior del LCL (5,71) también han sido propuestos como causantes de esta lesión (72) (Figura 4).…”
Section: Radiología Simpleunclassified
“…Therefore, while evaluating the injured knee, one should closely evaluate the anterolateral structures as well. 1,25,43,44 ClINICal aND sURgICal sIgNIFICaNCE Before modern ACL reconstruction techniques were developed, isolated lateral extra-articular procedures were used as the standard surgical techniques in patients with ACL insufficiency. These procedures were non-anatomic, reproduced the biomechanics poorly, and resulted in residual instability and over-constraint of the lateral compartment (with secondary osteoarthritis), thus being abandoned.…”
Section: The Segond Fracturementioning
confidence: 99%